RESPONS PERTUMBUHAN DAN PRODUKSI KACANG TANAH TERHADAP PEMBERIAN KOMPOS JERAMI PADI DAN FUNGI MIKORIZA ARBUSKULA - Tua Bastari Prima Bangun; Nini Rahmawati; Meiriani Meiriani (Universitas Sumatera Utara, 2013)
Growth Response and Yield of Peanut with Straw Compost and Mycorhiza Vesicular ArbuscularApplication. This research aims to study response in growth and yield of peanut for giving strawcompost and mycorhiza vesicular arbuscular. This research conducted on community land locatedat Pasar 1 Street, Tanjung Sari with altitude ± 25 meters above sea level in June until September2012 using Randomized Block Design (RBD) factorial with two factors , which are straw compostdoses (0, 750, 1500, 2250 g per plot) and mycorhiza vesicular arbuscular (0, 10 g micofer perplanting hole). The parameters observed were plant height, number of branches, weight of pods perplot and 100 seeds weight. The results showed that straw compost significantly affected plant height4-12 weeks after planting, and weight of pods per plot. Mycorhiza vesicular arbuscular andinteraction of them not significantly affected on all parameters observed.